Просвітницька діяльність чеських громадських організацій та часописів в Україні (кінець ХІХ – початок ХХ ст.) - Шульга, Світлана; Shulha, Svitlana (My University, 2016)
У статті на основі джерельного та монографічного матеріалу проаналізовано просвітницьку діяльність чеських громадських спілок, їхніх пресових органів. Визначено освітньо-культурний характер більшості чеських громадських об’єднань наприкінці ХІХ ст. та наголошено на активізації й зміні в напрямах і характері просвіт-ницького руху в міжвоєнний період.The article investigates the Czech Diaspora public awareness campaign of NGOs and newspapers in Ukraine in the late 19th and early 20th centuries. The principal directions of their activities, the main of which are culture and education, have been analyzed. The Czech press agencies involved in education, formed the Society named after John Amos Comenius in Kyiv and in the interwar period - Czech Matica School in Lutsk. The analyzed editorials suggest that the newspapers carried out a public awareness campaign and were the center for Czech community activities under conditions of other ethnic groups.
Public Awareness Campaign of Czech NGOs and Newspapers (Late XIX - Early XX Centuries)
Keywords: чехи; просвітницький рух; Україна; громадські спілки; Czechs; Volyn Czechs; Czech NGOs (public organizations); Czech Matica School; the Society named after John Amos Comenius; Volyn